Analysis of the debonding process of CFRP-to-timber interfaces. (15th June 2016) - Biscaia, Hugo C.; Cruz, David; Chastre, Carlos
Highlights: An analytical solution of the debonding process of CFRP/timber joints is presented. A tri-linear bond-slip model is used. The analytical solutions are compared with the experimental results. The influence of each state of the bond-slip model on the debonding process is shown. Abstract: The use of Fiber Reinforced Polymers (FRP) in the strengthening of timber structures is quite recent and few studies have discussed the debonding between these materials. The analysis of the Mode II debonding process between FRP composites and timber elements may be of great importance because this mode is predominant in the case, for instance, of the bending of beams. Knowing the appropriate bond-slip model to use on the estimation of the performance of FRP-to-timber interfaces is greatly relevant. Under such circumstances, a detailed knowledge of all the states that CFRP-to-timber interfaces are subjected to is important as well. The current work gives answers to these aspects proposing an analytical solution based on a tri-linear bond-slip model that is capable of describing precisely the full-range debonding behavior of FRP-to-timber interfaces. Thus, the purpose of this study is to contribute to existing knowledge with an analytical solution capable of describing the full-range debonding process between a FRP composite and a substrate. The analytical solutions herein proposed are also compared with the results obtained from several experiments based on single-lap shear tests. Comparisons at different load levels and different bonded lengths are presented. The slips, strains in the CFRP composite and bond stress distributions within the bonded interface are emphasized in the text. The complete load-slip response of CFRP-to-timber interface is also analyzed. Each state of the debonding process is described and each one is identified in the load-slip curve.